Use of Comparative Transcriptomics Combined With Physiological Analyses to Identify Key Factors Underlying Cadmium Accumulation in Brassica juncea L. - Zhang, Dawei; Du, Yunyan; He, Dan; Zhou, Dinggang; Wu, Jinfeng; Peng, Jiashi; Liu, Lili; Liu, Zhongsong; Yan, Mingli (Frontiers in Genetics, 2021)
The contamination of soils with cadmium (Cd) has become a serious environmental issue that needs to be addressed. Therefore, elucidating the mechanisms underlying Cd accumulation may facilitated the development of plants that accumulate both high and low amounts of Cd. In this study, a combination of phenotypic, physiological and comparative transcriptomic analyses were performed to investigate the effects of different Cd concentrations (0, 5, 10, 30, 50 mg/kg) on Brassica juncea L.. Our results suggest that B. juncea L. seedlings had a degree of tolerance to the 5 mg/kg Cd treatment, whereas higher Cd stress (10-50mg/kg) could suppress the growth of B. juncea L. seedlings. The contents of soluble protein, as well as MDA (malondialdehyde), were increased, but the activities of CAT (catalase) enzymes and the contents of soluble sugar and chlorophyll were decreased, when B. juncea L. was under 30 and 50 mg/kg Cd treatment. Comparative transcriptomic analysis indicated that XTH18 (xyloglucan endotransglucosylase/hydrolase enzymes), XTH22 and XTH23 were down-regulated, but PME17 (pectin methylesterases) and PME14 were up-regulated, which might contribute to cell wall integrity maintenance. Moreover, the down-regulation of HMA3 (heavy metal ATPase 3) and up-regulation of Nramp3 (natural resistance associated macrophage proteins 3), HMA2(heavy metal ATPase 2) and Nramp1(natural resistance associated macrophage proteins 1) might also play roles in reducing Cd toxicity in roots. Taken together, the results of our study may help to elucidate the mechanisms underlying the response of B. juncea L. to various concentrations of Cd.